REVITALIZING NATURE TOURISM: OVERCOMING CHALLENGES AND MAXIMIZING POTENTIAL IN WONODADI KULON VILLAGE PACITAN: REVITALISASI WISATA ALAM: MENGATASI TANTANGAN DAN MEMAKSIMALKAN POTENSI DI DESA WONODADI KULON PACITAN - Hananto Puriana, Ramadhany; Pieter Pelamonia, Shandy; Nuryadi, Achmad; Mulyono; Dharma Utamayasa, I Gede; Mahardika, Riga (Antis-publisher, 2024)
Indonesia is a country that is rich in natural beauty and diverse cultures, so that in this country we can see that there are many tourist attractions, both cultural tourism and natural tourism. With this, the role of villages is very necessary, especially in managing tourist villages, especially in Pacitan Regency. Apart from that, a phenomenon was also found that from 2021 until now there is a problem with funds, this is because the village budget has been used up for the needs of handling Covid in the form of direct assistance to communities affected by Covid. So that construction to maximize tourist attractions was temporarily stopped. Research shows that the management of natural tourist attractions in Pacitan Regency is running well, as the government has provided supporting facilities and infrastructure, but there are several obstacles, namely the difficulty of implementing water sports in this area. The method used in community service program activities is based on the asset based approach (ABA). The activity stages include field observations, drafting material requirements and implementation, licensing, implementation of service, evaluation, up to the final report. Based on the analysis, it was concluded that several things could be done to implement nature-based water tourism in the Wonodadi Kulon Village area, Ngadirojo District, Pacitan Regency. (1) Development of water tourism objects can be done by adding tourist variations such as canoes and water boats; (2) Development of transportation infrastructure by improving road access to tourist attractions which is still not good; (3) Development of capital assistance for activities by seeking sponsors in various sectors; and (4) Development of facilities and infrastructure that support tourism activities by rejuvenating facilities and innovating facilities that do not yet exist, such as parks and rest areas for tired visitors.